FOSTERING ACADEMIC LITERACY AND ACADEMIC WRITING IN UNIVERSITY: FROM THEORY TO PRACTICE - Natalia V. Smirnova (Высшее образование в России)
The paper addresses the theoretical and practical aspects of developing academic literacy of students. It overviews the nature and the structure of academic literacy and claims that academic literacy should be developed on the basis of academic discourse. Writing is seen as a key component and fostering academic literacy should be based on teaching academic written discourse transfer.